2021
DOI: 10.1007/s12325-021-01804-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Remdesivir on the Treatment of COVID-19 During the First Wave in Spain

Abstract: Introduction Spain was one of the most affected countries during the first wave of COVID-19, having the highest mortality rate in Europe. The aim of this retrospective study is to estimate the impact that remdesivir—the first drug for COVID-19 approved in the EU—would have had in the first wave. Methods This study simulated the impact that remdesivir could have had on the Spanish National Health System (SNHS) capacity (bed occupancy) and the number of deaths that could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The severity of clinical presentation of COVID-19 patients during the second and third pandemic wave in 2020–2021, before the completion of mass vaccination campaigns, and the absence of specific and effective drugs against SARS-CoV-2, have made remdesivir administration particularly frequent in the hospital setting, despite the absence of clear advantages against mortality. To date, real-life studies have provided conflicting results, with some reports suggesting clear benefits from remdesivir administration, and other yielding negative results [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The severity of clinical presentation of COVID-19 patients during the second and third pandemic wave in 2020–2021, before the completion of mass vaccination campaigns, and the absence of specific and effective drugs against SARS-CoV-2, have made remdesivir administration particularly frequent in the hospital setting, despite the absence of clear advantages against mortality. To date, real-life studies have provided conflicting results, with some reports suggesting clear benefits from remdesivir administration, and other yielding negative results [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, the reduced need of ICU admission in patients who were treated with both remdesivir and azithromycin suggests that the clinical benefits of remdesivir could be reinforced by the administration of other drugs exhibiting anti-SARS-CoV-2 activity in vitro, like azithromycin. Also, it may contribute to explain why real-life studies on remdesivir efficacy have produced conflicting results [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, three studies used 2020 US Dollars [ 28 , 30 , 37 ], one study used Euros (cost year not reported) [ 34 ], and one study used 2020 Chinese Yuan (CN¥) [ 35 ] in cost calculations. Most studies either used a healthcare system perspective ( n = 4) [ 28 , 32 , 34 , 35 ], or an individual hospital perspective ( n = 3) [ 27 , 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, it has been predicted that the use of remdesivir during the first wave of COVID-19 in Spain would have prevented 7639 deaths – a reduction of 27.51% ( 95% CI : 14.25–34.07%). 62 The World Health Organization (WHO) conducted a different randomized open-label non placebo controlled clinical trial of 4 antiviral drugs (remdesivir, hydroxychloroquine, lopinavir and interferon β-1a), involving 405 hospitals in 30 countries. The results in this case showed that remdesivir ( RR : 0.95 [ 95% CI , 0.81–1.11]) and the other compounds had little or no effect on overall mortality, initiation of ventilation, or duration of hospitalization; 27 however, patients in this study were stratified by need for respiratory support instead of the method used in other clinical trial (disease severity).…”
Section: Remdesivirmentioning
confidence: 99%